PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA PELANGGAN GRUP 20 DI LOTTEMart WHOLESALE SEMARANG) - Eustolia Ratih Novriana; Agus Hermani; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2013)
Business competition intensifies between companies, especially in the wholesale business or wholesale,requires companies to devise appropriate marketing strategies with corporate goals of maintaining customerloyalty. Developed marketing strategies that include product quality and service quality. Maintaining productquality and service quality with good will give satisfaction to the customer that will ultimately lead to customerloyalty. Wholesale LOTTEMart Semarang trying to maintain product quality and service quality to customers with agood group of 20, but the reality is still a decline in a group of 20 customers. Therefore, we need some research oncustomer loyalty group of 20This study aims to determine how the effect of product quality and service quality on customer loyalty(customer case study at Group 20 in LOTTEMart Wholesale Semarang). This type of research is explanatoryresearch with a sample of 100 respondents with a purposive sampling technique. Data collection techniques usedquestionnaires and interviews. The data obtained were analyzed using a test of validity, reliability, simple linearregression and multiple linear regression. While hypothesis testing using t-test and F testThe results showed that the positive effect of product quality on customer loyalty with t value 5.997. While thepositive impact of service quality on customer loyalty with t value 6.242. Then together, the quality of product andservice quality affects customer loyalty. Of the value of the coefficient of determination (0.328) it can be seen thatthe quality of product and service quality contributed by 32.8% on customer loyalty.Based on this analysis, the advice that can be given is that the LOTTEMart Wholesale Semarang to maintainproduct quality by increasing the range, keeping it neat banded packs, provide product warranty is longer, andimprove product quality by ensuring all SNI. In addition, the LOTTEMart Wholesale Semarang expected to conductregular training to employees that were originally once a year to once every 6 months.